PENGARUH ORIENTASI PASAR TERHADAP KINERJA PEMASARAN MASKAPAI PENERBANGAN AIR ASIA (Tujuan Penerbangan Kuala Lumpur Malaysia) - Sinta Diana; Devy W Apriandi (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2021)
Air Asia flights are one of the Low-Cost Carrier (LCC) airlines in Indonesia which are currently in high demand by passengers. The purpose of this research is to find out how the influence of market orientation for flight performance. Air Asia's flight population in this study is a student Air Asia user with flight routes from Jakarta to Kuala lumpur Malaysia. In this analysis the sample is done that is to 90 respondents. The technique of taking samples uses how to determine size using the Slovin formula. the method used is quantitative. The type of data used is primary data using the method of collecting data in the form of a questionnaire. The analytical tool used is simple linear regression. The results of this study are: market orientation positive effect on marketing performance, seen from the results of t count 16.854> t table <3.520, meaning market orientation has an effect on increasing marketing performance. Market orientation has a positive and significant influence on improving marketing performance.